Powstania śląskie i plebiscyt w pieśniach ze zbiorów prof. Adolfa Dygacza (PDF 1,56 MB) (Książnica Śląska, 2025)
The article is devoted to folk songs from the period of the SilesianUprisings and the Plebiscite which were collected by professor AdolfDygacz – ethnomusicologist, folklorist and publicist. The lyrics werecreated spontaneously to fit popular melodies, within the years 1919–1922. They were printed in local newspapers, such as „Powstaniec”and „Kocynder”, songbooks (Śpiewnik powstańczy by Jan Eichorn,1921; Pieśni powstańców górnośląskich by Jan Rzymełka, 1921) andleaflets. Nowadays, they are an important document of that period ofhistory and its social moods.The article concentrates on analysis of eight folk songs, that are available on an album titled Nadstawcie ucha kochani ludkowie releasedby the author of this article. One of the ballads, Kajze się podzioł mojsynocek miły? was used in a symphony by Henryk Mikołaj Górecki and Sól Ziemi Czarnej [Salt of the Black Earth], a film directed byKazimierz Kutz.